Triassic mineralization with Cretaceous overprint in the Dahu Au–Mo deposit, Xiaoqinling gold province: Constraints from SHRIMP monazite U–Th–Pb geochronology - Li, N.; Chen, Y.; Fletcher, Ian; Zeng, Q. (Elsevier Science BV, 2011)
The Xiaoqinling terrane in central China is the second largest gold producing area in China. Previous application of age constraints has yielded ages for the gold mineralization ranging from Paleoproterozoic, through Triassic (Indosinian), to Jurassic and Cretaceous (Yanshanian). SHRIMP U Th–Pb dating of hydrothermal monazite in a Mo-mineralized quartz vein from the Dahu Au–Mo deposit in the northern Xiaoqinling terrane identifies two mineralization episodes. Hydrothermal monazite intergrown with molybdenite yields an initial precipitation age of 216±5 Ma, which is identical to, but more precise than, the molybdenite Re–Os isochron age of 218±41 Ma. A younger generation of monazite is distinguished by data falling on a mixing array. It is inferred that the younger monazite was formed at the expense of the older ones during the Yanshanian, probably during a single event that occurred at ~125 Ma. Combining these results with available geochronological data and geological evidence, we conclude that molybdenum mineralization accompanied by monazite deposition took place in the Indosinian, followed by a Yanshanian tectono-hydrothermal event that resulted in large-scale gold mineralization in the Xiaoqinling terrane. Our observation demonstrates that monazite is sensitive to hydrothermal overprint, and thus is useful for dating fluid infiltration event.